Pulmonary Malformations: Predictors of Neonatal Respiratory Distress and Early Surgery - Costanzo, Sara; Flisetti, Claudia; Vella, Claudio; Rustico, Mariangela; Fontana, Paola; Lista, Gianluca; Zirpoli, Salvatore; Napolitano, Marcello; Riccipetitoni, Giovanna (Journal of Neonatal Surgery, 2016)
Objectives: The objective of our study is to retrospectively analyze a single-centre series of antenatally detected pulmonary malformations (PM) and to evaluate their postnatal outcome. Materials and Methods: We retrospectively reviewed all prenatally diagnosed PM patients referred to our Centre in the period between January 1999 and December 2014. All cases were diagnosed by one of our Maternal-Fetal Specialists by US examination. Congenital pulmonary airway malformation (CPAM) volume ratio (CVR), development of fetal complications, need for fetal therapy, need for neonatal resuscitation and timing of surgery were analyzed. Results: A total of 70 fetuses were diagnosed with a PM in the period of study. An initial CVR higher than 1.6 was found in 16/70 patients (22.8%); 14/16 developed fetal complications (pConclusion: CVR > 1.6 and the presence of fetal complications can be considered as predictors of respiratory distress at birth and of the need for early surgery. Nevertheless, the vast majority of PM are asymptomatic at birth and only a small group of fetuses require prenatal and postnatal treatment and support.